PENGARUH SUDUT BUKAAN GUIDE VANE DAN TEKANAN AIR TERHADAP KECEPATAN PUTAR DAN DAYA OUTPUT PADA PROTOTYPE PEMBANGKIT LISTRIK TENAGA MIKROHIDRO DENGAN TURBIN CROSSFLOW - I Wayan Arta Wijaya; I Made Dwi Mertadiyasa; I Made Suartika (Program Studi Teknik Elektro UNUD, 2020)
The pattern of power plants development in Indonesia is still relying on the availability of fossilfuels based energy sources. Meanwhile, Human are faced with a situation of depleting reserves offossil energy sources and increasing environmental damage due to the use of fossil fuels basedenergy sources. Renewable Energy development can be a solution to these problems. One of them isthe development of a Micro Hydro Power Plant. In the realization of Micro Hydro Power Plant inIndonesia, the crossflow water turbine type can be used. It is a type of impulse turbine with a goodcharacteristic at a low head for micro-scale generator capacity. This study analyzes the effect of guidevane opening angle and water pressure on rotation and output power of crossflow turbine. Theopening angle of the guide vane studied was 15º, 30º, 45º, 60º, 75º, and 90º in each water pressurecondition of 4 psi, 8.5 psi and 13 psi. The test is carried out by simulating direct measurements on theprototype of the Micro-hydro Power Plant that has been built. Every combination of parameterstested, the maximum value of rotational speed and output power is obtained at the guide vaneopening angle of 30º and water pressure of 13 psi. Turbine rotation values generated before and aftercoupled with a generator are 591.9 rpm and 522.7 rpm. The values of the generator rotation beforeand after the load coupled are at 3490 rpm and 2368 rpm. And the power value generated by thegenerator is 11.8 Watts.